Ummatan Wasatan dalam Perspektif Tafsir Maqāṣidī: Landasan Normatif Toleransi Antarumat Beragama - Wika Andeska (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This article examines the formulation of the concept of ummatan wasatan in the Qur’an through a maqāṣidī interpretation approach as a normative framework for interreligious tolerance. The study aims to (1) analyze the understanding of ummatan wasatan in the tradition of Qur’anic exegesis, (2) apply maqāṣid al-sharī‘ah as a methodological framework for interpreting the concept, and (3) formulate its relevance for strengthening religious tolerance in plural societies. This qualitative-normative research employs thematic and maqāṣidī interpretation methods by analyzing Qur’anic verses, classical and contemporary tafsir works, and maqāṣid al-sharī‘ah theories. The findings show that ummatan wasatan is not merely an identity marker or moderation slogan but a comprehensive ethical framework rooted in justice, balance, and moral responsibility. Through a maqāṣidī lens, the concept can be operationalized as a normative foundation for interreligious tolerance that emphasizes human dignity, social harmony, and public welfare. This study contributes theoretically and methodologically to Qur’anic studies and contemporary Islamic discourse on moderation and tolerance.